Treatment of Transplant Eligible Patients with Multiple Myeloma - Sonneveld, P.; Einsele, H.; Brioli, A. M.; Cavo, Michele (Springer Verlag, 2018)
Since more than 35 years high-dose therapy with melphalan (HDM) followed by autologous stem cell transplantation (ASCT) has been the cornerstone of treatment in eligible patients with newly diagnosed multiple myeloma (MM). In general these patients are up to 70 years of age, have little co-morbidities, and are able to tolerate intensive treatment. The standard approach in these patients is to initiate treatment with 3–4 induction cycles consisting of at least three drugs followed by hematopoietic stem cell mobilization, followed by HDM and ASCT. In this chapter Dr Sonneveld will discuss the various choices and combinations of induction, as well as the results of HDM/ASCT including single versus double ASCT. In part 2 Dr. Cavo will discuss the possibility to give consolidation treatment after the autologous transplantation and what the effect of such treatment will be on response quality and (progression-free) survival. Recently maintenance treatment with lenalidomide after HDM/ASCT was approved based on recent trials. The consequences of maintenance treatment and the potential choices will be discussed. Finally, in part 3 Dr. Einsele will discuss the role of allogeneic (donor) stem cell transplantation in newly diagnosed and relapsed MM. Several transplantation strategies are possible including the possibility to infuse donor lymphocyte cells. Graft-versus-host disease represents a significant clinical challenge in these patients. Choosing the right moment and an effective preparative regimen plus post transplantation treatment may offer a valuable treatment option for patients with high-risk disease.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic stem cell transplantation; Autologous stem cell transplantation; Consolidation treatment; High-dose therapy; Induction therapy; Maintenance treatment; Multiple myeloma